Current controller based on reduced order generalized integrators for distributed generation systems - Busada, Claudio (2012)
This paper presents a current controller based on a stationary reference frame implementation of an integrator in the synchronous reference frame [called here reduced order generalized integrator (ROGI)], suitable for three-phase distributed generation systems. The proposed controller is compared with the traditional second-order generalized integrator (SOGI)-based current controller. It is confirmed that, in normal operation conditions, both controllers have similar performance, requiring the ROGI-based controller much less computational burden than the SOGI counterpart. The proposed controller injects sinusoidal currents synchronized with the grid voltage, without requiring any dedicated synchronization algorithm. Three different current injection strategies are realizable with the same controller structure: balanced current injection, constant instantaneous active power injection, and maximum instantaneous active power injection. A state-variable-based control methodology in the discrete-time domain is presented. It ensures the stability and performance of the closed-loop system, even for high-order controllers and large digital signal processor processing delay. Moreover, it is confirmed that the proposed controller works satisfactorily even on faulty grid conditions.